Sensitivity and spectral control of network lasers - Dhruv Saxena; Alexis Arnaudon; Oscar Cipolato; Michele Gaio; Alain Quentel; Sophia Yaliraki; Dario Pisignano; Andrea Camposeo; Mauricio Barahona; Riccardo Sapienza (Nature Communications, 2022)
Nanophotonic light sources with programmable emission spectrum are important building blocks for integrated photonics, sensing and optical computing. Here the authors tune the complex laser spectrum of a network laser achieving selective lasing of a single, two or more modes.